Radular Morphology and Relationship Between Shell Size and Radula Size of Few Dominating Intertidal Gastropod Mollusks of Veraval Coast, Gujarat - Gajera, Niyati; Vakani, Bhavik; Kundu, Rahul (Frontiers in Marine Science, 2022)
The radula is the main feeding organ and also very significant to the majority of the mollusks (especially gastropod) taxonomy. With shell morphology, radular morphology is the key characteristic for the identification of gastropod species. The shape and structure of the radular teeth are unique from family to species level. In this study, five basic types of radula (i.e., docoglossan, rhipidoglossan, taenioglossan, stenoglossan, and toxoglossan), which were observed from a total of 23 different species belonging to 12 families, were examined. Collection of the voucher intertidal gastropod specimen for the study had initiated during May–October 2019 in the rocky intertidal area near Veraval of the south Saurashtra coastline. Direct handpicking methods were used for the collection of the specimen for experiments.